Kara Avrupası Ceza Muhakemesi HukukundaSilahların Eşitliği İlkesi Uygulanabilir mi? - (:unkn) unknown (My University, 2020)
Adil yargılanma hakkının doğal bir unsuru olarak kabul edilen silahların eşitliğiilkesi, taraf muhakemesinin egemen olduğu İngiliz ceza muhakemesinden türetilmiştir. Bununla birlikte Avrupa İnsan Hakları Sözleşmesine taraf olan her devletten, ceza muhakemesi sistemlerinden bağımsız olarak silahların eşitliği ilkesinigüvence altına almaları beklenmektedir. Çalışmamızda, tahkik sisteminden gelenKara Avrupası ceza muhakemesi hukukunda, silahların eşitliği ilkesinin uygulanabilmesinin mümkün olup olmadığı tartışılacaktır.

The equality of arms principle, which is a natural element of right to have a fair trial, is derived from adversary English Criminal Procedure. Nonetheless all signatory states of the European Contract of Human Rights, independently of their criminal procedure systems, are expected to secure the equality of arms principle. In our study, it is examined whether it is possible to imply equality of arms principle at the criminal procedure systems from inquisitorial tradition.
Is It Possible to Imply The Equality of Arms Principle in Continental European Criminal Procedure?